Knowledge, beliefs and attitudes of physicians in low and middle-income countries regarding interacting with pharmaceutical companies: a systematic review - Lotfi, Tamara (BMC Health Serv Res, 2016)
BACKGROUND: Understanding the perceptions and attitudes of physicians is important. This knowledge assists in the efforts to reduce the impact of their interactions with the pharmaceutical industry on clinical practice. It appears that most studies on such perceptions and attitudes have been conducted in high-income countries. The objective was to systematically review the knowledge, beliefs and attitudes of physicians in low and middle-income countries regarding interactions with pharmaceutical companies. METHODS: Eligible studies addressed any type of interaction between physicians and pharmaceutical companies. The outcomes of interest included knowledge, beliefs and attitudes of practicing physicians. The search strategy covered MEDLINE and EMBASE databases. Two reviewers completed in duplicate and independently study selection, data abstraction, and assessment of methodological features. The data synthesis consisted of a narrative summary of the findings stratified by knowledge, beliefs and attitudes. RESULTS: We included ten reports from nine eligible studies, each of which had a number of methodological limitations. Four studies found that the top perceived benefits of this interaction were receiving information and rewards. In five out of eight studies assessing the perception regarding the impact of the interaction on the behavior of physician prescription, the majority of participants believed it to be minor. In one of these studies, participants perceived that impact to be lesser when asked about their own behavior. The attitudes of physicians towards information and rewards provided by pharmaceutical company representatives (PCRs) (assessed in 5 and 2 studies respectively) varied across studies. In the only study assessing their attitudes towards pharmaceutical-sponsored Continuing Medical Education, physicians considered local conferences to have higher impact. Their attitudes towards developing policies restricting physicians’ interactions with PCRs were positive in two studies. In one study, the majority of participants did not mind the public knowing that physicians were receiving gifts and awards from drug companies. CONCLUSIONS: This review identified few studies conducted in low and middle-income countries. While physicians generally perceived the impact of interactions on their behavior to be minor, their attitudes toward receiving information and rewards varied across studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-016-1299-4) contains supplementary material, which is available to authorized users.